PENGARUH RELAKSASI BENSON TERHADAP TINGKAT KECEMASAN PENULARAN CORONA VIRUS DISEASE 2019 PADA MAHASISWA NERS TINGKAT III STIKES SANTA ELISABETH MEDAN TAHUN 2020 - Samfriati S; Friska G; Lia Mayang S S (STIKes Santa Elisabeth Medan, 2020)
Background: In the Covid-19 Pandemic era 2020, Covid-19 with its increasing spread rate even death in each individual can occur, this greatly affects the condition of students universally by experiencing annoyance, worry, fear, anxiety so that it can cause excessive anxiety. One of the techniques to reduce this level of anxiety is the Benson Relaxation, which can provide comfort and a sense of relaxation so that it can adapt well to the current environment. This Benson relaxation is a combination of deep breaths and elements of faith that give a feeling of calm, comfort and even confidence.Goals: The purpose of this study was to determine the effect of Benson Relaxation on the Anxiety Levels of Corona virus disease 2019 on nursing students level III of STIKes Santa Elisabeth Medan 2020.Method: This study used a pre-experimental study with one group pre test and post test design. The instrument used was an anxiety level questionnaire, with 30 nursing students level III STIKes Santa Elisabeth Medan. The research sample were 30 students, where the sample was used by using purposive sampling.Result: The results of the study p-value = 0.000 (P <0.05) indicate that Benson relaxation has an effect on the anxiety level of the third level of Nursing student STIKes Santa Elisabeth Medan.Conclusion: This Benson relaxation technique is a good and appropriate relaxation to do at this time to reduce the level of anxiety in the respondent so that the respondent experiences a sense of calm and comfort. Respondents are expected to always apply this Benson relaxation to overcome the increasing increase in anxiety and can overcome the level of anxiety they are experiencing